The complete genome sequence of CrRV-Ch01, a new member of the family Rhabdoviridae in the parasitic copepod Caligus rogercresseyi present on farmed Atlantic salmon (Salmo salar) in Chile - Økland, Arnfinn Lodden; Skoge, Renate Hvidsten; Nylund, Are (Archives of virology, 2018)
We have determined the complete genome sequence of a new rhabdovirus, tentatively named Caligus rogercresseyi rhabdovirus Ch01 (CrRV-Ch01), which was found in the parasite Caligus rogercresseyi , present on farmed Atlantic salmon ( Salmo salar ) in Chile. The genome encodes the five canonical rhabdovirus proteins in addition to an unknown protein, in the order N-P-M-U (unknown)-G-L. Phylogenetic analysis showed that the virus clusters with two rhabdoviruses (Lepeophtheirus salmonis rhabdovirus No9 and Lepeophtheirus salmonis rhabdovirus No127) obtained from another parasitic caligid, Lepeophtheirus salmonis , present on farmed Atlantic salmon on the west coast of Norway.